Efeitos cardiotóxicos do veneno total e da proteína dermonecrótica recombinante da aranha Loxosceles intermedia - Camila Dias Lopes (2009)
Loxosceles spider bites cause numerous accidents in humans worldwide. In Brasil, loxoscelism brown spider envenomation constitutes the third cause of accidents by venomous animals. Injections of the whole Loxosceles intermedia venom or of recombinant toxin derivated of it (rLiD1) produce in animal models skin-tissue changes and systemic symptoms similar to those detected in humans. The aim of our work was to characterize de cardiac effects induced in mice by L. intermedia venom and rLiD1. L. intermedia antigens were detected in the kidney, heart, lung and liver of experimental envenomed mice by ELISA. Since serum creatine kinase and creatine kinase MB isoenzyme activities were elevated in treated mice, a cardiac action of the venom was further investigated. The binding of rLiD1 to cardiomyocytes was demonstrated by means of an immunofluorescence technique using confocal microscopy. Isolated Langendorff-perfused heart preparations from envenomed mice presented an impairment of the in vitro heart functions. Ventricular cardiomyocites isolated from envenomed mice showed a significant increase of L-type calcium current density and intracellular Ca2+ transients. Taken together, our findings establish the cardiotoxic effects of Loxosceles intermedia spider venom. A protein from sphingomyelinase family plays a key role in the heart mice dysfunction, as attested by cardiac activity of the recombinant toxin rLiD1.